2021
DOI: 10.1109/access.2021.3054426
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Number of Turns Design of the IPT Coils for Laptop Wireless Charging

Abstract: The coil design of the inductive power transfer (IPT) for a transmitter (Tx) and receiver (Rx) is crucial to determine the performance of the IPT. Considering core loss and copper loss of the Tx and Rx coils, which are major loss terms of the whole IPT system, determination of the winding turns for the Tx and Rx coils becomes a key factor for maximum power transfer design of the IPT coils. In this paper, an optimal turns design of IPT coils for laptop wireless charging applications with a maximum power transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The voltage and current of the compensation network are under the continuous conduction mode (CCM) operation in the steady state, only considering the fundamental frequency components [23]. They can be expressed as follows [24]:…”
Section: Ipt System For Uavsmentioning
confidence: 99%
“…The voltage and current of the compensation network are under the continuous conduction mode (CCM) operation in the steady state, only considering the fundamental frequency components [23]. They can be expressed as follows [24]:…”
Section: Ipt System For Uavsmentioning
confidence: 99%
“…• Consumer electronics: With the proliferation of electronic devices like smartphones, tablets, wearable gadgets, and laptops, the demand for WPT solutions for their charging has grown significantly. This trend has driven the development of WPT technology for these consumer electronics [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the PTE bound is defined as the maximum PTE. Many studies have attempted to calculate the PTE of inductive and resonance WPT [8,9] and MPT [10][11][12][13][14][15] systems. For instance, Goubau [11] and Shinohara [10] showed that a Gaussian beam is an optimal transmission source between two planar apertures, especially in the radiative near field, and they calculated PTE using the proposed theory.…”
Section: Introductionmentioning
confidence: 99%